Phytochemical Screening, GC Analysis and Antibacterial Activity of Citrus limon Peel Extract and Essential Oil - Thapa, Surendra; Poudel, Kamala; Limbu, Shova Kumari; Dahal, Ganesh; Pokhrel, Shanta (Journal of Nepal Chemical Society, 2022)
Lemon (Citrus limon) is the most commonly grown tree fruit in the world. The fresh lemons were collected from the local market of Kathmandu, Nepal. Hexane and methanol extracts of plant material i.e. lemon peel were screened for the analysis of the presence of phytochemicals as well as their antibacterial activity. Methanol extract of lemon peel showed the maximum positive phytochemical test with the presence of alkaloids, flavonoids, polyphenols, terpenoids, glycosides, saponin, tannins etc. The essential oil was obtained by steam distillation from fresh peels of lemon using the Clevenger apparatus and analyzed by gas chromatography (GC). Twenty six (26) chemical components were identified in the essential oil of lemon peel. Lemon peel essential oil indicated the presence of Pinene (β) (15.46 %), Limonene (28.94 %), and Terpinene (γ) (8.64), Terpinen-4-ol (3.29 %), Neral (4.20 %), Geranial (5.28 %) as major components. The lemon peel essential oil was found to be a potent antibacterial agent against the Bacillus subtilis (21 mm).